U(VI) speciation studies by Raman spectroscopy technique in the production of nuclear fuel. (March 2022) - Bonales, Laura J.; Rodríguez-Villagra, Nieves; Sánchez-García, Iván; Montoro, Oscar R.
Abstract: One key intermediate solid product in the industrial production of the UO2 for fabrication of common nuclear fuel is the ammonium diuranate or ADU. Its composition and morphology are crucial for industrial operations since this determines the quality of UO2 powder. In this work we demonstrate that Raman spectroscopy technique is a power tool to characterize the precipitation of ADU and to monitor the precipitation reaction progress, being able to follow the U(VI) speciation and to correlate these results with the features of the obtained solid. Thereby, here we propose the use of the Raman spectroscopy technique in the production of nuclear fuel in order to monitor the speciation of U(VI) during the ADU precipitation with dual-purpose; in one hand, to improve the safety in the fuel management and on the other hand, for the quality control for the manufacturing industry in nuclear power. Highlights: Raman spectroscopy is a perfect tool to monitor ADU precipitation. Monitoring by Raman allow to accurately study U(VI) speciation and ADU product. U(VI) speciation results can be correlated with the features of the obtained solid. Raman can be used as an online technique for the industrial UO2 production.